SOSIALISASI PENGEMBANGAN BISNIS KULINER BAKSO DAN SOSIS BAKAR DI DIGITAL PLATFORM E-COMMERCE PENGABDIAN MAHASISWA UIGM DALAM MENDUKUNG MBKM - Nabilah Sajidah Hasna; Sutra Meilani Rizki; Lesi Hertati; Terttiaavini; Agustina Heryati; Asmawati (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
Business today is greatly facilitated by the existence of digital platforms that oversee shopping activities, making it easier for people who want to shop and trade. By utilizing this technology, it can affect food sales which are carried out online without having to come directly to the sales place. With this, consumers can also directly sort and choose what food they want to buy. This can minimize mistakes that can be made by both consumers and sellers, with the current situation many consumers are lazy to buy due to long distances or because of other things. This form of online method business also uses various online media, ranging from social media, web, to marketplaces. There are also many businesses that use conventional methods, but not a few have shifted to using online media. Some businesses also use both methods to more easily reach customers and promote more widely. Given the rapid technology in this modern era that makes it easy for us to open a business with online methods.